2019
DOI: 10.1038/s41467-019-11571-5
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of an Escherichia coli ST131 lineage during recurrent urinary tract infection

Abstract: Recurrent urinary tract infections (rUTIs) are extremely common, with ~ 25% of all women experiencing a recurrence within 1 year of their original infection. Escherichia coli ST131 is a globally dominant multidrug resistant clone associated with high rates of rUTI. Here, we show the dynamics of an ST131 population over a 5-year period from one elderly woman with rUTI since the 1970s. Using whole genome sequencing, we identify an indigenous clonal lineage (P1A) linked to rUTI and persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 73 publications
4
72
0
2
Order By: Relevance
“…Unfortunately, four patients with UTIs associated with E. coli strains O25: H4 and O75: NM did not respond to the treatment with the autologous BL and the UTIs persisted. Several studies have associated UPEC O25: H4 strains to persistent UTIs due to the formation of intracellular bacterial communities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, four patients with UTIs associated with E. coli strains O25: H4 and O75: NM did not respond to the treatment with the autologous BL and the UTIs persisted. Several studies have associated UPEC O25: H4 strains to persistent UTIs due to the formation of intracellular bacterial communities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Once introduced into the intestine, these strains may establish colonization for some time but then may be replaced later by other E. coli genotypes introduced into the intestine by food. A recent study has shown that ESBL‐producing ST131 strain was detected in the intestine of a 74‐year‐old woman for over 5 years, although repeated exposures to sources containing this genotype could not be ruled out (Forde et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of them encode enzymes of metabolic pathways (aes, icd, pabB, trpA, trpB, fumC, mdh, purA, aspC, fadD, uidA, aroE, mtlD); ten belong to replication, repair, or transcription systems (polB, gyrA, recA, dinB, dnaG, mutS, arcA, cyaA, grpE, rpoS), and the remaining four control the production of two symporters (putP, lysP), kinase (adk) and protease (clpX). The sequences of these genes were obtained from 124 E. coli genomes (listed in Supplementary Table S1), including 59 complete genomes, whose phylogroups were previously identified in original papers [45,52,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] (shown in bold in Supplementary Table S1). The remaining 65 genomes unassigned to phylogroups and containing orthologs of discriminatory genes were added to increase the resolution of phylogenetic trees.…”
Section: Alignment-based Multilocus Sequence Typing Resulted In Tree mentioning
confidence: 99%